(untitled) (Research, Society and Development, 2021)
Cardiovascular disease (CVD) management therapy follows the parameters proposed in cardiovascular health (CVS) by the American Heart association (AHA) which includes behavioral metrics: smoking, diet and physical activity and biological metrics composed of BMI, blood pressure, serum cholesterol and blood glucose. Monitoring these metrics is associated with a reduction in CVD deaths and hospitalizations. With the same purpose, in Brazil, the family health strategy (ESF) promotes monthly meetings with educational actions, encouragement to practice physical exercises, scheduled medical appointments, and delivery of medicines in primary care. This study aims, through an integrative review, to discuss the existing difficulties in the control of cardiovascular diseases (CVD), considering the multifactorial aspect of the process of prevention and treatment.